Natural Deep Eutectic Solvent as Extraction Media for the Main Phenolic Compounds from Olive Oil Processing Wastes - Sonia Bonacci; Maria Luisa Di Gioia; Paola Costanzo; Loredana Maiuolo; Sofia Tallarico; Monica Nardi (MDPI AG, 2020)
In this new century, sustainable development challenges chemical sciences to develop new and clean technological processes. The agri-food industry produces significant quantities of waste, raising significant economic and environmental concerns. Food waste valorization using environmentally friendly procedures is of increasing importance. This study describes the use of several Natural Deep Eutectic Solvents (NADESs) for the microwave-assisted extraction (MAE) of valuable bioactive phenolic compounds from olive oil processing wastes. The extracted samples were characterized by liquid chromatography electrospray ionization quadrupole time-of-flight mass spectrometry (LC-ESI-QTOF/MS) analysis and the quantification of the phenolic compounds was performed by HPLC analysis. The obtained data were compared with those obtained using water as the solvent in the same extraction conditions. The extraction process is nontoxic, simple and selective and meets most of the criteria to be considered as a sustainable process, with the solvents arising directly from nature.